Chemical constituents from the tubers of Pinellia ternata (Araceae) and their chemotaxonomic interest. (October 2015) - Wu, Ying-Ying; Huang, Xiao-Xiao; Zhang, Meng-Yu; Zhou, Le; Li, Dan-Qi; Cheng, Zhuo-Yang; Li, Ling-Zhi; Peng, Ying; Song, Shao-jiang
Abstract: This work describes the isolation and characterization of twenty compounds from the tubers of Pinellia ternata (Thunb.) Breit, including 17 lignanoids (1 –17 ) and three alkaloids (18 –20 ). All structures were established based on analysis of their spectroscopic data. It is the first report of compounds3–11 and13–18 from the genus Pinellia, and the first report of compounds3–4, 6–9, 11 and13–18 from the family Araceae. In addition, the biosynthetic pathways of the 17 lignanoids are summarized. A liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOFMS/MS) method in both positive and negative ion mode was also used to confirm the identity of these seventeen lignanoids from the tubers of P . ternata . The results from the present work provide further information about the diversity of compounds in the genus Pinellia . Graphical abstract: Highlights: First report of 15 compounds in the genus Pinellia . First report of 13 compounds in the family Araceae. A LC-ESI-QTOFMS/MS method was applied to confirm seventeen lignanoids (1–17 ) from the tubers of Pinellia ternata . Likely biosynthetic relationships among compounds1 –17 were proposed.